Migrants and educational achievement gaps - Horst Entorf (IZA World of Labor, 2015)
As global migration flows increase, so do the number of migrant students in host country schools. Yet migrants' achievement scores lag well behind those of their native-born schoolmates. Performance gaps are explained largely by differences in migrant parents' socio-economic background, cultural capital, and language skills. Education policy needs to focus on language teaching, parental involvement, diversity training, and beneficial social interaction between immigrant and native-born populations. With the wealth of many industrialized countries threatened by a lack of qualified labor, education of immigrants should be an important priority.
Keywords: H41; H52; I24; I25; I28; J15; 330; education; immigration; socio-economic status; cultural capital; schooling systems; peer effects